The Effect of the Snowball Drilling-Based Jigsaw Model on Learning Independence and Mathematical Spatial Ability of Elementary School Students - Ike Kurniawati; Herlin Kurniasari (JEES: Journal of Education and Educational Sciences, 2026)
This study aims to determine the influence of variables in the snowball drilling-based Jigsaw learning model. The research method employed a pre-experimental design using a one-group pretest–posttest design. The research subjects were school students with a saturated sampling technique and a sample size of 60 respondents. The research instruments consisted of a cognitive test of mathematical spatial ability and a questionnaire on students' mathematical learning independence as well as a questionnaire on responses to the Jigsaw learning model. Data analysis techniques used multiple linear regression tests to determine the effect of the snowball drilling-based Jigsaw model on students' learning independence and mathematical spatial ability. Path analysis was used to test the relationship between aspects of independence and mathematical spatial ability. The results showed that the application of the snowball drilling-based Jigsaw model had a significant effect (p < 0.05) on improving elementary school students' mathematical learning independence and mathematical spatial ability. This study contributes novelty by integrating the Jigsaw cooperative model with Snowball Drilling to simultaneously strengthen students’ learning independence and mathematical spatial ability at the elementary level, an area that has been rarely examined in previous studies. In addition, there is a positive relationship between aspects of the variables of learning independence and mathematical spatial ability, as can be seen from the p-value < 0.05. The Jigsaw model can encourage students to increase their learning independence through responsibility and develop mathematical spatial abilities through understanding relationships, perception, visualization, rotation, and spatial orientation. Thus, this study can be used as a reference in similar studies.